Reforma al art. 27 del código de la niñez y adolescencia en relación a los apremios impuestos al garante por la prestación del pago de alimentos - Gavilanez Cordova, Enma Beatriz (2016)
The problems that I have identified for the presentation of the plan of legal research has its foundation in the field of childhood and adolescence, with focus on the treatment of aspects of singular importance that involve the right to food and the responsibilities assigned to those forced to this benefit. Converge a myriad of situations in practice derived from the obligation of the provision of food which is necessary to analyze critically and reflexive, with the purpose of adapting the existing regulatory framework with the social and economic changes to which we must adapt those who live in society. Precisely, I stopped to analyze what i think constitutes an excess in the area of normative regulation within the art. 27 The law reforming the title V of the code of childhood and adolescence in relation to the constraints and responsibilities imposed on the guarantor of the obligation of the provision of food, then transcribe the legal provision for from it to clarify the legal problem object of analysis; Note that the principal can be released from the personal constraints imposed by the law to ensure the payment of food as the order of rooting, prohibition of dispose, retention of funds, when present before the judge or judge a guarantor or guarantor; in the first place I am not in agreement of the excess of discretion conferred on judges or judges to estimate in an arbitrary manner and biased in many occasions the acceptance of the guarantee or not; secondly it seems to me that having the guarantor or guarantor assumed the obligation of the principal debtor and having paid already the guarantee with the commitment to take its place as a responsible for payment by concept of food, it is unnecessary that has this You extend limitations to their rights of freedom, which are truncated on the prohibition of leaving the country for example, because while acting as a guarantor of according to article referred to above, it shall be subjected to the same responsibilities and constraints that the main debtor.